Fabrication Tolerant Integrated Polarization Rotator Design Using the Jones Calculus - Baier, Moritz; Soares, Francisco M.; Gartner, Tom; Moehrle, Martin; Schell, Martin (Journal of lightwave technology, 2019)
A fabrication tolerant polarization rotator (PR) building block is added to our generic photonic integration technology. Using asymmetric waveguides, we propose a PR with guided modes that do not enclose a 45° angle with the substrate. Rather, we find that polarization performance and loss can be improved substantially by allowing the mode angles to vary along the device. We numerically optimize PR designs, targeting at high extinction and high fabrication tolerance. The optimization makes use of the Jones formalism and the fact that Jones calculus is numerically much faster than beam propagation methods. A comparison of our Jones model and commercial simulation software shows excellent agreement. Fabricated devices show a polarization extinction between 10 and 14 dB across different wafers, at an excess loss of 1 dB. Compared to PR designs without tapers, the loss is 3 dB lower and the polarization extinction is now reproducible from wafer to wafer.